2020
DOI: 10.1177/1178638820926521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tree Nuts Consumption on Serum Lipid Profile in Hyperlipidemic Individuals: A Systematic Review

Abstract: Many epidemiological studies have regularly connected nuts intake with decreased risk for coronary heart disease. The primary mechanism by which nuts protect against cardiovascular disease is through the improvement of lipid and apolipoprotein profile. Therefore, numerous dietary intervention studies investigated the impact of nut consumption on blood lipid levels. Many studies have shown that nut intake can enhance the lipid profile in a dose-response way among individuals with increased serum lipids. This sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…Several meta-analyses have reported significant improvements in blood lipids and apolipoprotein profiles with nut consumption [ 12 , 13 , 14 ]. The magnitude of the effect was greater among those with higher baseline concentrations and those with healthy body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses have reported significant improvements in blood lipids and apolipoprotein profiles with nut consumption [ 12 , 13 , 14 ]. The magnitude of the effect was greater among those with higher baseline concentrations and those with healthy body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised controlled trials have shown improvements in risk factors of chronic disease with regular nut consumption. For example, total cholesterol and low-density lipoprotein cholesterol (LDL-C) are consistently lowered by regular nut consumption, with reductions more pronounced in those with elevated cholesterol concentrations [ 12 , 13 , 14 ]. Findings on blood pressure and biomarkers of oxidation, inflammation, and endothelial function are mixed, with some showing positive effects, while others report no effect [ 13 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The total cholesterol levels were also reduced significantly in the almond group. In a recent systematic review on tree nut, Altamimi et al ( 45 ) reported that almonds lowered LDL- c and that effects were observed with the consumption of even 20 g of the nut. The beneficial effects of almonds could be attributed to the fact that our participants were asked to consume raw almonds with skin.…”
Section: Discussionmentioning
confidence: 99%
“…Nut consumption has been generally associated with cardiovascular benefits, but results toward metabolic outcomes are not univocal in the scientific literature: in fact, despite acute feeding studies have shown favorable effects on fasting blood glucose [ 23 ], no association between nut consumption and the risk of Type 2 diabetes mellitus was observed in meta-analyses of prospective studies [ 24 ]. Moreover, nuts have been shown to affect blood lipids despite the effects being stronger among individuals with blood lipid abnormalities [ 25 ]. Up to date, the strongest evidence from epidemiological studies relates nut consumption with lower risk of hypertension [ 26 ].…”
Section: Discussionmentioning
confidence: 99%